2013
DOI: 10.1002/ar.22813
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐Specific Cytolysis Caused by an E1B55K‐Attenuated Adenovirus in Nasopharyngeal Carcinoma is Augmented by Cisplatin

Abstract: An E1B55K-attenuated adenovirus, dl1520, has been shown to replicate selectively in and lyse tumor cells. In this study, the antitumor activities of dl1520, alone or in combination with the chemotherapeutic agent cisplatin, were investigated in nasopharyngeal carcinoma (NPC) cells. The results demonstrated that dl1520 replicated in and destroyed NPC cells, and induced apoptosis in vitro. In a nude mouse xenograft model, dl1520 significantly inhibited the growth of NPC cell xenografts, and the viral replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The E1B55kD-deficient Ad ( dl 1520), also named Onyx-015 [31,36,37] was kind gift from Professor Arnold J. Berk (University of California-Los Angeles). The two viruses were both propagated in 293 cells, and the viral titers were determined using the hexon immunoassay with the BD Clontech™ Adeno-X Rapid Titer Kit (San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The E1B55kD-deficient Ad ( dl 1520), also named Onyx-015 [31,36,37] was kind gift from Professor Arnold J. Berk (University of California-Los Angeles). The two viruses were both propagated in 293 cells, and the viral titers were determined using the hexon immunoassay with the BD Clontech™ Adeno-X Rapid Titer Kit (San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A replication-defective recombinant Ad vector encoding the secretory form of human endostatin (Ad-Endo) was generated in our lab as described previously [ 23 , 25 ]. The E1B55kD-deficient Ad ( dl 1520), also named Onyx-015 [ 31 , 36 , 37 ] was kind gift from Professor Arnold J. Berk (University of California-Los Angeles). The two viruses were both propagated in 293 cells, and the viral titers were determined using the hexon immunoassay with the BD Clontech™ Adeno-X Rapid Titer Kit (San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Along similar lines, tumor-infiltrating cells including macrophages, 160 , 161 myeloid-derived suppressor cells, 162 - 164 and mesenchymal stem cells (MSCs) have been harnessed as vehicles to selectively deliver oncolytic viruses to neoplastic lesions while shielding them from neutralizing antibodies and protecting them from sequestration by the MPS 163 , 165 - 170 . Finally, several laboratories worldwide have demonstrated that the therapeutic profile of oncolytic virotherapy can be remarkably boosted by the co-administration of several chemotherapeutics, including (but not limited to) gemcitabine (an immunostimulatory nucleoside analog), 171 - 173 paclitaxel (a microtubular inhibitor), 174 - 176 temozolomide and cyclophosphamide (two alkylating agents), 72 , 177 - 179 sunitinib (a relatively unspecific tyrosine kinase inhibitor), 180 - 182 cisplatin (a non-immunogenic DNA-damaging agent), 183 - 186 various histone deacetylase inhibitors, 187 and 13- cis retinoic acid (a retinoid employed for the treatment of high risk neuroblastoma) 188 , 189 . Taken together, these findings indicate that oncolytic viruses can mediate therapeutically relevant anticancer effects in vivo.…”
Section: Introductionmentioning
confidence: 99%